Inflectional and Derivational Affixation in “While My Guitar Gently Weeps” by The Beatles: A Morphological Study - Nur Mohammad Maulana Ibrahim; I Made Juliarta (Universitas Bali Dwipa, 2026)
This study examines inflectional and derivational affixation in the lyrics of “While My Guitar Gently Weeps” by The Beatles from a morphological perspective. Using a descriptive qualitative approach, the song lyrics were analyzed by identifying and classifying words that undergo affixation based on established morphological theory. The findings reveal that inflectional affixes occur more frequently than derivational affixes, indicating that the lyrics rely primarily on grammatical variation rather than lexical expansion. Inflectional suffixes such as -s, -ed, and -ing are used to express grammatical features without changing word class, while derivational affixes such as -ly and un- contribute to lexical and functional changes. The analysis also shows that the suffix -ing can function both inflectionally and derivationally, depending on its syntactic context. Overall, the study demonstrates that song lyrics can serve as a meaningful source of data for morphological analysis and highlights the importance of contextual interpretation in distinguishing between inflectional and derivational affixation.